Christianity and medical science: A historical quest for remedy in time of epidemics - V.U. Iheanacho (Acta Theologica)
On 27 March 2020, Pope Francis led a special prayer to seek divine intervention for the cessation of the global corona virus pandemic. At the end of the prayer, the pontiff, carrying a monstrance with the Blessed Sacrament, pronounced an extraordinary Urbi et Orbi blessing. At its worst, nature can be overwhelming and destructive in its universal ability to strike fear and terror that ridicules the best efforts of science. In such moments of universal terror and dread, human beings, in their helplessness and regardless of place and time, instinctively seek to escape their fate. In most instances, they do so either through faith or reason (science) alone, or through a combination of both. Supernatural powers are invoked through prayers and entreaties to assist mortals in their afflictions. For its part, reason dictates what needs to be done in terms of practical and necessary measures to alleviate pain and suffering while waiting for divine intervention. This article explores the historical response of Christianity during epidemic outbreaks. It does so more specifically through the lens of Catholic religious tradition and practices, in order to highlight a few instances when the Catholic Church partnered with science to shield human beings from nature’s threat of extinction.